PRODUCTIVE PERFORMANCES OF SWAMP BUFFALOES OF ASSAM (Indian Journal of Animal Production and Management, 2013)
A survey was carried out to study productive performances of swamp buffaloes of Assam. Average lactation length, lactation milk yield, peak yield, and days to attain peak yield were found to be 237.06 ± 0.74 days, 448.38 ± 1.67 kg, 3.41 ± 0.02 kg and 54.16 ± 0.19 days respectively. Lactation length was found to be affected significantly by type of animal, location and season of calving while lactation order exerted non significant effect. Lactation milk yield and peak yield was found to be affected significantly by type of animal, location, lactation order and season of calving. Days to attain peak yield was found to be affected significantly only by season of calving while location, type of animal, lactation order exerted non significant effect.
Keywords: Swamp buffalo; Assam; Productive traits